Is my rival’s rival a friend? Popular third-party perceptions of territorial disputes in East Asia - Horesh, Niv; Kim, Hyun Jin; Mauch, Peter; Sullivan, Jonathan (Asia Research Centre, Copenhagen Business School, 2014)
This article examines how China's rise and increasing tensions with Japan are portrayed by South Korean bloggers. The deterioration in relations between China and Japan over the last two years generally projects onto the ways and means by which China's rise is portrayed in South Korea. Since Korea's relations with both its more populous neighbours have been historically fraught, and since it is also implicated in various territorial disputes with both countries, determining Korean sensibilities is an important way of gauging shifts in public opinion across the region. Although the conservative political establishments in both South Korea and Japan might see China as a constant threat, South Korean and Japanese netizens still popularly view each other with suspicion. By contrast, popular perceptions of the China threat in either country can be swayed by escalation of territorial disputes these two US allies still have with one another